Atlas of the invisible : maps & graphics that will change how you see the world - Uberti, Oliver (W. W. Norton & Company, 2021)
"An unprecedented portrait of the hidden patterns in human society-visualized through the world of data. Award-winning geographer-designer team James Cheshire and Oliver Uberti transform enormous datasets into rich maps and cutting-edge visualizations. In this triumph of visual storytelling, they uncover truths about our past, reveal who we are today, and highlight what we face in the years ahead. With their joyfully inquisitive approach, Cheshire and Uberti explore happiness levels around the globe, trace the undersea cables and cell towers that connect us, examine hidden scars of geopolitics, and illustrate how a warming planet affects everything from hurricanes to the hajj. Years in the making, Atlas of the Invisible invites readers to marvel at the promise and peril of data, and to revel in the secrets and contours of a newly visible world"--